Reliability of two-dimensional kinematic measurement of the overhead deep squat movement by photogrammetry: A new way of analyzing joint mobility limitations (Research, Society and Development, 2022)
The objective was to determine the reliability of the angular measurement (RAM) of deep overhead squat (OHS) evaluated by the photogrammetry technique, determining its intraclass correlation coefficient (ICC), as well as the respective absolute and relative typical error (ETM) of the measurement. 20 physically active elderly individuals performed 2 visits. In the first meeting, the anthropometric assessment and familiarization with the OHS movement with the hands above the head were performed. On the second visit, participants performed two consecutive runs of the OHS movement with their hands above their heads, where they held a stick. The measurements were repeated on the same visit. All the elderly were filmed by a camera with a capacity of 200 frames per second. Internal consistency was performed using photogrammetry, together with the Kinóvea® software for two-dimensional angular analysis. RAM was determined from a CCI, as well as absolute and relative ETM. The CCI analyzes showed an excellent association between the first measurement and the second measurement of angular parameters in the OHS movement. The ETM showed low relative values ​​of measurement variation (1.7 to 4.2%), except for the hip measurement, in which it presented ±10% variations. To confirm the absence of differences, a dependent t test was used, suggesting agreement between measurements (p > 0.05). The OHS RAM for most of the investigated joints showed excellent ICC, as well as low absolute and relative ETM of angular kinematics. The hip RAM measurement varied widely, but without significant differences between the first and second measurements.